Application of a hermeneutic phenomenologically orientated approach to a qualitative study - Jones, F.; Rodger, S.; Ziviani, J.; Boyd, Roslyn (2012)
Phenomenology enables researchers and clinicians to understand the lived experience of those affected by situations that are not easily measurable. This paper presents an example of the decision making undertaken to investigate the lived experience of adolescents with cerebral palsy in their transition to secondary school. The process engaged in undertaking this research is used as a means of highlighting key decision points when undertaking qualitative investigation of this kind. Hermeneutic phenomenologically orientated study: Eleven parent-adolescent dyads of youth with cerebral palsy (8 males, 2 females, ages 12-14 years; Gross Motor Function Classification System (GMFCS) I=3, II=4, III=3, IV=1; Manual Abilities Classification System (MACS) I=5, II=2, III=4, IV=1, V=5; spasticity=10, dystonia=1; rural=1, regional=3, metropolitan=7). A step-by-step qualitative decision making pathway, including Colaizzi's methods, to facilitate investigation of the lived experience of adolescents with cerebral palsy was developed. The paper presents four main phases in the decision making process required when designing or interpreting a qualitative research study, namely philosophy, methodology, research methods, and confirmation. A clear process in the construction of qualitative research has been developed. This should support researchers working in various fields of allied health and rehabilitation to investigate the experiences of service recipients where there is insufficient research to formulate hypotheses.